The health benefits of volunteering at a free, weekly, 5 km event in the UK: A cross-sectional study of volunteers at parkrun. - Steve Haake; Helen Quirk; Alice Bullas (Public Library of Science (PLoS), 2022)
This paper investigates the motives for first participating in parkrun and its impact for those who volunteered compared to those who did not volunteer. A cross-sectional survey was emailed to parkrun registrants, resulting in 60,680 survey returns from parkrun participants who self-identified as volunteers only (n = 681), runners/walkers who volunteered (n = 21,928) or runners/walkers who did not volunteer (38,071). Two survey questions were analysed in this paper: (1) their motives for first participating in parkrun as a volunteer or runner/walker; and (2) the perceived impact on their health and wellbeing. More than half of respondents were female and were predominantly from a white ethnic background. Compared to runners/walkers who volunteered, those who volunteered exclusively were older, more likely to be retired and more likely to be inactive at registration. Exclusive volunteers were motivated by wanting to give something back to the community (45.8%), to feel part of a community (26.1%), to help people (24.5%) or because they were unable to run (21.1%). Runners/walkers who volunteered were more likely to volunteer because they felt obliged to (49.3%). A large proportion of exclusive volunteers reported improvements to connections with others such as feeling part of a community (83.5%), the number of new people met (85.2%) and time spent with friends (45.2%). While mental and physical health were ranked low by volunteers as a motive (4.7% and 2.7% respectively), improvements were reported by 54.5 and 29.3% respectively. The data shows that volunteering at parkrun without participating as a runner or walker can deliver some of the components of the Five Ways to Wellbeing advocated by the NHS. The characteristics of parkrun (free, regular, local, accessible and optional) make it a viable social prescribing offer that can be used as a model for other community events seeking to attract volunteers.